ANALYSIS OF THE DIFFUSION CAPACITY OF THE LUNGS FOR CARBON MONOXIDE - CLINICAL BIOMARKER IN SETTINGS OF POST-ACUTE CARE OF PATIENTS WITH COVID-19 - Arbutina, Suzana; Dimitrievska, Deska; Zdraveska, Marija; Arsovski, Zoran; Todevski, Dejan; Stojkovic, Jagoda; Dokikj, Dejan; Danilovski, Dragan (Македонско лекарско друштво = Macedonian medical association, 2021)
COVID-19 is an infectious disease resulting in respiratory, neurological, cardiovascular, and digestive disorders that are likely to stem from a systemic endothelial dysfunction. Even though the lungs are the major organ affected by COVID-19, the clinical manifestations of this disease are widely unpredictable, ranging from asymptomatic to severe respiratory dysfunction (in about 5% of the cases), which leads to an intensive care. In all patients affected with pulmonary problems, the lung function is disturbed in varying degrees of intensity, while the findings deviate in both the functional and radiological examinations. The diffusing capacity of the lungs for carbon monoxide (DLCO) is one of the parameters that reflect the damage to the alveolocapillary membrane. DLCO/VA considers the differences in lung size. For this reason, it is sometimes considered as a more accurate expression of its own function of gas exchange in the lungs. The observation that the DLCO may be impaired while the DLCO/VA may not be impaired in patients after COVID-19, may be an indication that the diffuse membrane change plays a significant role in causing lung dysfunction in comparison to the reduced VA. The systemic functional assessment should be taken in consideration for all moderately severe patients infected with COVID-19 at the time of their discharge from hospital, and such a multidisciplinary approach can be provided by individualized rehabilitation programs. Lung function tests can be considered as necessary tools for monitoring of the functional impairment, planning of the rehabilitation, managing of the possible complications, as well as for prevention of the long-term side effects.
АНАЛИЗА НА ДИФУЗИОНИТ КАПАЦИТЕТ НА БЕЛИТЕ ДРОБОВИ ЗА ЈАГЛЕНОРОДЕН МОНОКСИД - КЛИНИЧКИ БИОМАРКЕР ВО ПОСТАВКИ ЗА ПОСТАКУТНА НЕГА НА ПАЦИЕНТИ СО COVID-19
Keywords: diffusion capacity of the lungs; KOVID- 19; rehabilitation treatment